Chapter 9 Afghanistan's Cosmopolitan Trading Networks A View from Yiwu, China - Marsden, Magnus (Edinburgh University Press, 2018)
The focus of this chapter is the city of Yiwu and the nature of Afghan networks present there. By inserting such networks both in the context of the wider global settings, and in terms of the traders' experience of space in Yiwu, we seek to contribute to an emerging body of literature on Muslim cosmopolitanism in two ways. First, we bring attention to the ways in which the expressions of Muslim cosmopolitanism visible in Yiwu are premised on violent histories of international conflict and interference that have led to massive displacements of the country's people, as well the bleaching out of the country's own religious diversity. Secondly, we recognise that if the traders with whom we work are cosmopolitan in some aspects of their lives, then in others they reinforce and sustain collective commitment to national, regional, ideological and confessional identities, identities that are also of critical significance to their activities as traders.